The effectiveness of spinal manipulation technique compared to therapeutic exercises in relieving chronic low back pain. A Systematic Review - Chávez Vera, Cynthia Karolina; López Cifuentes, Andrés Sebastián (SATHIRI, 2025)
The European clinical guideline for the management of non-specific chronic pain recommends manual therapy as a treatment option. However, evidence shows that passive treatments for chronic low back pain have lost ground compared to active exercises, which are recommended for both treatment and prevention of low back pain. Furthermore, there is still no consensus on the best technique or treatment; however, some evidence has shown excellent results, including spinal manipulation technique and therapeutic exercises (general exercises and motor control). The objetive of this systematic review was to evaluate the effectiveness of manual therapy techniques compared to therapeutic exercises for the relief of chronic low back pain. A systematic review of literature from randomized controlled trials (RCTs) used 5 databases: Medline, Scopus, PubMed, Pedro, and Cochrane, published in English, Spanish, and Portuguese. Search terms included: low back pain, spinal manual therapy, non-specific pain, exercises for low back pain, chronic pain. Results Four eligible studies were found after selecting titles, abstracts, and full texts according to inclusion and exclusion criteria. Moderate evidence was found that exercises have a slight significant improvement over spinal manipulation therapy and control groups with sham physiotherapy in the short term, but not in the medium or long term, where spinal manipulation therapy showed a slight improvement over exercises and the sham control group. This systematic review concludes that both manual therapy and supervised exercises provide positive outcomes for improving the well-being of patients suffering from musculoskeletal injuries
Keywords: low back pain; spinal manual therapy; non-specific pain; exercises for low back pain; chronic pain